Melhorando a experiência do usuário: desenvolvimento de uma plataforma de vendas para a empresa SamarcStore - LIMA, Francy Adria de (2024)
The popularity of sales apps and the online market in Brazil has grown rapidly in recent years, with many companies seeking to expand their online presence to meet consumer needs. E-commerce in Brazil is one of the largest in Latin America and has the potential to continue growing in the future. Sales apps provide a convenient and accessible platform for users to buy products and services, offering a wide range of options, competitive prices, and the convenience of shopping from their mobile device. In addition, many apps offer additional features such as user reviews and comments, product recommendations based on user preferences, and flexible delivery options. The online market in Brazil is being driven by factors such as the growing popularity of online shopping, the availability of mobile devices and internet access, as well as increased consumer confidence in online purchases. Furthermore, companies are investing in advanced technologies such as artificial intelligence and data analysis to improve the user experience and make the purchasing process more efficient and secure. Overall, sales apps and the online market in Brazil have great potential to continue growing in the future, offering a convenient and accessible platform for users to shop and for companies to expand their online presence. During the process of creating the sales app for SamarcStore, several steps were followed, from market research to prototyping. Based on information about consumer needs, e-commerce market trends, and best practices for mobile interface design, an app was developed that meets consumer needs and offers an easy-to-use and visually appealing interface. The end result was a prototype of an electronic product sales app that represents a contribution to improving the user experience on e-commerce platforms.